Shortage of organ donation resulting from difficulties in the diagnosis of brain death by medical practitioners in Malaysia - Mhd Khotib, N.A.; Abdul Rahman, N.N.; Shaikh Mohd Salleh, S.M.S. (2014)
The issues of brain death and organ donation are closely related. Brain death is the irreversible loss of brain function, and from the medical perspective, a person who is brain dead cannot be recovered. The shortage of organs for transplantation is a worldwide problem. One of the reasons contributing to the shortage of organs is the refusal of medical practitioners to diagnose brain death. This paper will highlight four factors why medical practitioners in Malaysia may refuse to diagnose brain death. These factors include: 1) medical practitioners may not accept brain death as true death, 2) a misconception of the concept of brain death, 3) a lack of knowledge about brain death, 4) a lack of responsibility in carrying out professional duties. These four factors will be discussed on the backdrop of ethics as the ethical implications pertaining to brain death diagnosis in Malaysia.